Efecto del silicio sobre la incidencia de enfermedades en el cultivo de arroz (Oryza sativa L.) - Bravo Sellan, Néstor Isaac (2023)
Rice, Oryza sativa L., one of the most important crops in the world, is the second most popular cereal after wheat. The objectives were to explain the effects of silicon on crop diseases and to demonstrate how crucial silicon is for preventing disease outbreaks in rice. This document, which served as a practical component of the degree work, was prepared using information collected from current texts, magazines, online libraries and scientific articles. According to the findings, in rice, disease-causing biotic agents (bacteria, spiroplasmas, fungi, protozoa, mycoplasmas, nematodes and viruses) affect the crop, influencing the reduction of production and the beneficial effects of silicon have ha It has been demonstrated in several plant species, and in case of phytosanitary problems, it is capable of increasing the resistance of plants. Silicon acts by forming a physical barrier in the epidermal cells of the leaves that prevents the penetration of fungal hyphae or stylets of sucking insects such as aphids. This results in biochemical changes, such as the accumulation of phenolic compounds, lignin, and phytoalexins.